Impact of Socioeconomic Deprivation on children's Need for Anesthesia: A Retrospective Analysis of Electronic Health Records From a Tertiary Referral children's Hospital - Bryan Atandi; Philip Arnold (Pediatric Anesthesia, 2026)
ABSTRACT Background Socioeconomic status and geography create healthcare inequalities in children. Geographical areas in the United Kingdom are ranked by deprivation, which confers a higher risk for specific diseases that necessitate procedures under anesthesia. Aims To examine the relationship between the geographical indices of deprivation and the odds of children presenting for procedures involving anesthesia at a specialist children's referral hospital in Northwest England and Wales, UK. Methods A retrospective cross‐sectional analysis linking electronic patient records of patients presenting for anesthesia from 2016 to 2024 to population data. Multivariate mixed‐effects logistic regression was conducted for the odds of having a procedure requiring anesthesia. Results 71 613 episodes were included in the final analysis, confined to areas with a higher proportion of children having a procedure at our hospital and only one episode per child in each year. The adjusted odds ratio for having a procedure according to deprivation was 1.15 (95% CI: 1.13–1.17, p < 0.001), with children from a deprived area being more likely to undergo treatment. The odds of undergoing a procedure were higher for most specialities, for children from a deprived area. It was the greatest for dental procedures. When analyzed by the 10 deciles of IMD, the strongest effect was for children from the most deprived areas. Conclusion Children living in deprived areas are more likely to present for procedures involving anesthesia at our hospital, which serves a large area: Northwest England and Wales. This is true for most specialities. Sensitivity analysis to address study design limitations did not change the general conclusion. Further research is needed to clarify this phenomenon. Our study emphasizes the importance of preventive interventions to reduce inequalities in child health due to socioeconomic deprivation and geography.